Climatic changes inferred from the chroma and magnetic susceptibility of aeolian deposits in the Central Shandong Mountains over the penultimate interglacial period. Issue 1 (1st October 2022) - Zhao, Qiuyue; Zhang, Xinqi; Sun, Yanping; Liu, Xiuying; Ge, Tianyan; Liu, Ning; Tang, Anrui; Zhou, Rui
Abstract: Loess-palaeosol sediments document the climatic changes and provide a good basis for palaeoclimate reconstruction. Palaeoclimatic changes of the holocene and the last interglacial period have been widely studied, but the penultimate interglacial period has been studied scarcely. The Dongheishan (DHS) section in the western of Shandong Province (China) preserves a loess-palaeosol sequence that includes the penultimate interglacial period. The annual average temperature and precipitation are retrieved by chroma and magnetic susceptibility (MS) to reconstruct the palaeoclimatic variations since the penultimate interglacial period. The results indicate that the lightness valley values and the redness and yellowness peaks correspond to the peak MS values, which can consistently reflect climate changes; redness and MS correlated well with the annual average temperature and annual precipitation, respectively. The annual average temperature is 14.4 °C based on redness in the the penultimate interglacial palaeosol, indicating that the palaeoclimate was warmer during the penultimate interglacial period than at present. The annual average precipitation is 349 mm derived from magnetic susceptibility, showing that the magnetic susceptibility should be cautious of the inversion of precipitation in the Central Shandong Mountains (CSM) region.